Understanding the disconnect between lifestyle advice and patient engagement: a discourse analysis of how expert knowledge is constructed by patients with CHD - Robson M; Riley S; McKeogh D (Informa UK limited, trading as Taylor & Francis group, 2024)
OBJECTIVE: Adherence to healthy lifestyle advice is effective in prevention of non-communicable diseases like coronary heart disease (CHD). Yet patient disengagement is the norm. We take a novel discursive approach to explore patients' negotiation of lifestyle advice and behaviour change. METHOD: A discourse analysis was performed on 35 longitudinal interviews with 22 heterosexual British people in a long-term relationship, where one had a diagnosis of CHD. The analysis examined the relationships between patients' constructions of expert knowledge and the implications of these accounts for patients' dis/engagement with lifestyle advice. RESULTS: Expert knowledge was constructed in four ways: (1) Expert advice was valued, but adherence created new risks that undermined it; (2) expert knowledge was problematised as multiple, contradictory, and contested and therefore difficult to follow; (3) expert advice was problematised as too generalised to meet patients' specific needs; and (4) expert advice was understood as limited and only one form of valued knowledge. CONCLUSION: Patients and partners simultaneously valued and problematised expert knowledge, drawing on elaborate lay epistemologies relating to their illness which produced complex patterns of (dis)engagement with expert lifestyle advice. Recognition of the multiple and fluid forms of knowledge mobilised by CHD patients could inform more effective interventions.
Keywords: CHD; Lifestyle advice; expert knowledge; lay epistemologies